Inacap : innovation in educational management through service design - Labarca Rodríguez De Mesa , Diego (Base Diseño e Innovación, 2016)
In mid-2014, after two years of an in-depth study of the Service Design discipline by its top management, the Instituto Nacional de Capacitación Profesional (Inacap) contacted Procorp to redesign the service experience provided to its students until then in the context of implementing their educational project, since it was an aspect that had not been fully developed in its 2012- 2016 Strategic Planning.